Investigating the Relationship between Environmental Lead Exposures and the Onset of Alzheimer's Disease Pathologies - Johnson, Dakota, C (My University, 2014)
It is been estimated that nearly 5 million Americans suffer from Alzheimer's Disease (AD), making finding its cause one of medicine's top priorities. It has long been known that genetics plays a major role in the development of Alzheimer's Disease, but this does not fully explain why or when the disease manifests itself. Alzheimer's is likely not a single-origin disease, but rather a disease that arises from a combination of both genetic and environmental factors that occur in the "right mix" at the "right time" to produce a phenotype indicative of AD. A major component of Alzheimer's is the plaques of amyloid-_ protein that form in the brains of its victims. One of the cells in the brain that has been shown to control the levels of amyloid-_ is the microglia. Studies show that these microglia experience a "critical window" of heightened susceptibility to environmental contaminants early in development from post-natal day (PND) 5-15. In this study, 3x-Tg-AD mice were dosed during this critical window with a proven neurotoxicant, lead acetate, in the form of drinking water. The levels and states of microglia were observed and compared to the levels of control mice, and the levels of amyloid-_ were tested using enzyme-linked immunosorbent assay (ELISA). This study hoped to uncover the relationship between microglia and amyloid-_ levels as well as determine whether introduction of an environmental toxicant during a period of heightened susceptibility could exacerbate the onset of AD pathologies later in life.
Keywords: Alzheimer's disease; Microglia; Amyloids; Amyloid beta; Neurodegeneration; Critical windows; Amyloid-β